(3GdJQGK GdMj (B/s - (3YGjOGHj, O(B. (3jhSas; Dr. Yousif Aydabi (Sharjah Institute for Heritage(3cs, 2016)
Essays on social, cultural and built heritage of Sharjah.
Title translation: Our Life's HeritageD. Yousif Aydabi
Arabic
Keywords: HN50-995 Social history and conditions. Social problems. Social reform- By region or country UAE- Sharjah